2011
DOI: 10.1073/pnas.1108107108
|View full text |Cite
|
Sign up to set email alerts
|

Rac1/osmosensing scaffold for MEKK3 contributes via phospholipase C-γ1 to activation of the osmoprotective transcription factor NFAT5

Abstract: Separate reports that hypertonicity activates p38 via a Rac1-OSM-MEKK3-MKK3-p38 pathway and that p38α contributes to activation of TonEBP/OREBP led us to the hypothesis that Rac1 might activate TonEBP/OREBP via p38. The present studies examine that possibility. High NaCl is hypertonic. We find that siRNA knockdown of Rac1 reduces high NaCl-induced increase of TonEBP/OREBP transcriptional activity (by reducing its transactivating activity but not its nuclear localization). Similarly, siRNA knockdown of osmosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 40 publications
(54 reference statements)
2
37
1
Order By: Relevance
“…c-Abl and PLC-␥1 stimulate NFAT5 transactivating activity, and SHP-1 inhibits it (21,31,74). PLC-␥1 mediates the increase of NFAT5 transactivating activity caused by Rac and OSM (75). c-Abl and PI3K both contribute to high NaClinduced activation of ATM (21,30).…”
Section: Discussionmentioning
confidence: 99%
“…c-Abl and PLC-␥1 stimulate NFAT5 transactivating activity, and SHP-1 inhibits it (21,31,74). PLC-␥1 mediates the increase of NFAT5 transactivating activity caused by Rac and OSM (75). c-Abl and PI3K both contribute to high NaClinduced activation of ATM (21,30).…”
Section: Discussionmentioning
confidence: 99%
“…This finding provides the preliminary structural information for CCM2ct, although the physiological significance of this structural feature has not been uncovered. Since initial characterization of CCM2-MEKK3 interaction in hyperosmotic stress signaling, further studies confirmed that CCM2-MEKK3 interaction is crucial for the activation of osmoprotective transcription factor via not p38 MAPK but phospholipase C-g1 (Zhou et al, 2011). Later, CCM2-MEKK3 interaction was found to be associated with an Arp2/3 defect-induced non-autonomous effect on chemotactic signaling through the activation of nuclear factor kB downstream (Wu et al, 2013).…”
Section: Introductionmentioning
confidence: 87%
“…CCM2 binds F-actin in in vitro binding assays, suggesting that it organizes a complex that is capable of linking RAC1-dependent actin reorganization to p38 activity (Hilder et al, 2007b). Recent work confirms that osmotic stress elicits a response of the CCM2-RAC1 pathway, but indicates that the signaling might occur through phospholipase C (PLC)c1 (Zhou et al, 2011). Conversely, another study suggests that CCM2 loss does not affect the p38 MAPK pathway, but rather affects JNK and MAPK kinase (MKK) signaling (Whitehead et al, 2009).…”
Section: Ccm2mentioning
confidence: 92%